2002
DOI: 10.1021/bi026427v
|View full text |Cite
|
Sign up to set email alerts
|

Halide-Stabilizing Residues of Haloalkane Dehalogenases Studied by Quantum Mechanic Calculations and Site-Directed Mutagenesis

Abstract: Haloalkane dehalogenases catalyze cleavage of the carbon-halogen bond in halogenated aliphatic compounds, resulting in the formation of an alcohol, a halide, and a proton as the reaction products. Three structural features of haloalkane dehalogenases are essential for their catalytic performance: (i) a catalytic triad, (ii) an oxyanion hole, and (iii) the halide-stabilizing residues. Halide-stabilizing residues are not structurally conserved among different haloalkane dehalogenases. The level of stabilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…It is therefore not surprising that mutations resulting in modification of this hole result in different effects on different halogenated substrates. This has been demonstrated previously by mutagenesis of the residues in direct contact with the halogen (so-called first-shell residues F151 and F169) (1,21) and also with the second-shell residues F154 (18), I211, and F143 (this study). The constructed mutants, including the sixfold mutant, can be used for further analysis of structure-function relationships of haloalkane dehalogenases.…”
Section: Figsupporting
confidence: 80%
“…It is therefore not surprising that mutations resulting in modification of this hole result in different effects on different halogenated substrates. This has been demonstrated previously by mutagenesis of the residues in direct contact with the halogen (so-called first-shell residues F151 and F169) (1,21) and also with the second-shell residues F154 (18), I211, and F143 (this study). The constructed mutants, including the sixfold mutant, can be used for further analysis of structure-function relationships of haloalkane dehalogenases.…”
Section: Figsupporting
confidence: 80%
“…By analogy to the well-studied mechanism of another haloalkane dehalogenase (DhlA) from Xanthobacter autotrophicus (65), the catalytic mechanism of LinB is proposed to involve an interaction of the substrate with the catalytic triad (D108, H272, and E132, i.e., nucleophile-histidine-acid) and a group of halide-stabilizing residues (principally N38 and W109) (18,32,60,130). It was suggested that nucleophilic attack by D108 at the carbon atom of the substrate results in C-Cl bond cleavage by an S N 2 displacement mechanism, resulting in the formation of an acyl-enzyme intermediate.…”
Section: Linb Haloalkane Dehalogenase Biochemistrymentioning
confidence: 99%
“…Such technologies are already in use (14) or are under development (2, 15, 16). Furthermore, haloalkane dehalogenases has become an important model system for in silico study of molecular principles of enzymatic catalysis (12,(17)(18)(19)(20)(21)(22)(23)(24).Haloalkane dehalogenase LinB (25) is the enzyme isolated from a ␥-hexachlorocyclohexane-degrading bacterium Sphingomonas paucimobilis UT26 (26). The LinB enzyme catalyzes conversion of 1,3,4,6-tetrachloro-1,4-cyclohexadiene to 2,5-dichloro-2,5-cyclohexadiene-1,4-diol via 2,4,5-trichloro-2,5-cyclohexadien-1-ol.…”
mentioning
confidence: 99%
“…The enzymes cleaves the carbon-halogen bond and replaces a halogen with a hydroxyl group from a water molecule (1). Activity and specificity of haloalkane dehalogenases is not optimal for industrial applications (2), and numerous studies have been conducted to improve their catalytic properties using in vitro techniques (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Engineered enzymes can be used in biotechnology applications, such as detoxification of environmental pollutants and bioorganic synthesis.…”
mentioning
confidence: 99%